2019
DOI: 10.1063/1.5086822
|View full text |Cite
|
Sign up to set email alerts
|

Absolute calibration of GafChromic film for very high flux laser driven ion beams

Abstract: Raman spectrometer for the automated scan of large painted surfaces Review of Scientific Instruments 90, 053101 (2019);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Several works carried out to study the RCF dose rate dependence confirmed that RCFs can be considered dose rate independent over a wide dose range [89,100,101]. Bin et al reported on absolute calibration measurements for HD-V2 Gafchromic™ films in extremely high dose rate, approaching 7 × 10 11 Gy/s, for laserdriven ion beams [102]. RCF radiation type and energy dependence has been deeply investigated over the last few years mainly for the RCF types used in medical dosimetry, such as Gafchromic™ EBT series and XRQA-2.…”
Section: Radiochromic Films Response To Relevant Physical Quantitiesmentioning
confidence: 98%
“…Several works carried out to study the RCF dose rate dependence confirmed that RCFs can be considered dose rate independent over a wide dose range [89,100,101]. Bin et al reported on absolute calibration measurements for HD-V2 Gafchromic™ films in extremely high dose rate, approaching 7 × 10 11 Gy/s, for laserdriven ion beams [102]. RCF radiation type and energy dependence has been deeply investigated over the last few years mainly for the RCF types used in medical dosimetry, such as Gafchromic™ EBT series and XRQA-2.…”
Section: Radiochromic Films Response To Relevant Physical Quantitiesmentioning
confidence: 98%
“…Calibration of the films is another important issue and would require tests at a facility where the delivered dose can be accurately determined. Other groups have performed similar experiments, see for example [34] and [35]. 10 and 11 show a comparison of the beta function (which gives the beam envelope as a function of distance along the beam-line) from the beam optics design, which was performed using BeamOptics, and the beta values after each element in the BDSIM simulation.…”
Section: End Stationmentioning
confidence: 99%
“…After exposure, the pieces of film were digitized with an Epson V850 Pro flatbed scanner with 600dpi resolution. The raw RCF signal was first converted to optical density (OD=−log 10 (Exposed Signal/Unexposed Signal)) and then to deposited dose [40,41] in order to retrieve the proton fluence.…”
Section: Pulse Durationmentioning
confidence: 99%